Entorno social y su influencia en la recaída de pacientes drogodependientes que asisten al CETAD “Solo por la Gracia de Dios” - Alvarez Zuñiga, Yomaira de los Angeles (2024)
Relapse is considered one of the versatile problems that develops worldwide in relation to the different factors that are associated with the reinsertion of behavioral patterns of consumption. That is why the present research has as its purpose to analyze the influence of the social environment on the relapse of drug addicts attending the CETAD "SOLO POR LA GRACIAS DE DIOS" city of Quevedo-Province of Los Ríos. The research assumes a quantitative, non-experimental, descriptive approach, which allows obtaining statistical data of the object of study. In order to carry out the research, techniques and instruments (surveys and tests) were used that have characteristics to evaluate, interpret and determine the variables of the present study, which is why the following instruments were used: survey, Multidimensional Scale of Perceived Social Support. A sample of 50 patients in residential treatment was used. Of the inmates surveyed, 100% were male, 70% were single, 10% were married, 10% were in a common-law relationship and 10% were separated. With respect to the level of schooling, it was found that 50% of the inmates completed their secondary education, while 40% finished elementary school and 10% graduated with a technical degree. With respect to the level of schooling, it was found that 50% of the inmates completed their studies in high school, while 40% finished elementary school and 10% finished technical school. According to the results obtained, it can be concluded that the social environment does have an impact on relapse because it is one of the main risk factors that influenced the reinsertion of psychoactive substance use.